Do flat detector cardiac X-ray systems convey advantages over image-intensifier-based systems? Study comparing X-ray dose and image quality - Davies, Andrew G.; Cowen, Arnold R.; Kengyelics, Stephen M.; Moore, Janet; Sivananthan, Mohan U. (European radiology, 2007)
The recent introduction of "flat-panel detector" (FD)-based cardiac catheterisation laboratories should offer improvements in image quality and/or dose efficiency over X-ray systems of conventional design. We compared three X-ray systems, one image-intensifier (II)-based system (system A), and two FD-based designs (systems B and C), assessing their image quality and dose efficiency. Phantom measurements were performed to assess dose rates in fluoroscopy and cine acquisition. Phantom dose rates were broadly similar for all systems, with all systems classified as offering "low" dose rates in fluoroscopy on standard phantoms. Patient X-ray dose rate and subjective image quality was assessed for 90 patients. Dose area product (DAP) rates were similar for all systems, except system C, which had a lower DAP rate in fluoroscopy. In terms of subjective image quality, the order of preference was (best to worst): system C, system A, system B. This study indicates that the use of an FD detector does not infer an automatic improvement in image quality or dose efficiency over II based designs. Specification and configuration of all of the components in the X-ray system contribute to the dose levels used and image quality achieved.